PENGARUH DESTINATION BRAND EXPERIENCE PADA INTENSI REKOMENDASI DAN INTENSI KUNJUNGAN KEMBALI DALAM KONTEKS PARIWISATA PANTAI ALAM INDAH TEGAL - Ghea Dwi Rahmadiane (FEB Universitas Muhammadiyah Pekajangan Pekalongan, 2019)
Lack of research regarding destination brand measurement indicates that conceptualizing how tourists evaluate a destination brand is complex. Researcher examines destination branding via a new conceptualization, destination brand experience (DBE), which provides a more holistic and unified view of the destination brand. This study aimed to analyze the effect of a destination brand experience on intention recommend and revisit intention. This research conducted in four destination object in Pantai Alam Indah Tegal with Total amount of sample 130. This research using survey method with quantitative approach. Analysis tool used in this research is Partial Least Square (PLS) with Warp PLS 5.0 Program. Results showed that the destination brand experience has positive influence and significant on intention to recommend and also the destination brand experience has positive influence and significant on revisit intention.